Abstract ID: 144 An equipment-specific Geant4 model for the Elekta Agility collimator. (October 2017) - Martins, Juliana Cristina; Alhazmi, Abdulaziz; Neppl, Sebastian; Belka, Claus; Reiner, Michael; Parodi, Katia; Veloza, Stella
Abstract : This study aims to develop and validate a linac-specific Geant4 Monte-Carlo (MC) model of an Elekta Agility collimator (Elekta AB, Sweden) to be used for dose distribution simulations of IMRT and VMAT procedures. The Agility collimator consists of two diaphragms mounted orthogonally to 160 interdigitating leaves. Elekta Precise IAEA phase-space files for 6 MV photon beam were used as primary beam generator. The diaphragms and leaves were primarily modelled following vendor-provided geometry, designed specifically for clinical implementation of MC-based Treatment Planning Systems. However due to small differences in installation and setting, geometric parameters are necessarily linac-specific. Hence such parameters have been defined as tunable mathematical functions, so the user can find the best fit for an individual installation. For model validation, system's dosimetric characteristics were simulated in Geant4 v.10.01.p02. Fields ranging from 2 × 2 to 20 × 20 cm 2 were delivered to a virtual water phantom. Percentage Depth Dose (PDD) and lateral profiles were compared to corresponding measurements conducted with a water phantom (Blue Phantom2, IBA Dosimetry, USA) in an Elekta Synergy (Eleka AB, Sweden) coupled with Elekta Agility. Intraleaf and interleaf leakage and tongue-and-groove (T&G) effect were also investigated. Results show good agreement between measurements and simulations, being comparable to published results[1] . In both cases the maximum leakage and the underdosage due to T&G effect were 0.55% and 20%, respectively. Small discrepancies between measured and simulated PDDs and lateral profiles were observed in small fields, which could be attributed to the use of unsuited phase-spaces. The developed MC model was proven able to reproduce the Elekta Agility collimator. Modelled electron source parameters, as the energy and shape of the incident electron beam, can significantly influence the output of linac dose simulations[2] . A more adequate phase-space for 6 MV photon beam, matching specific configurations of the linac in use, is under development. Validation for IMRT and VMAT plans and for 15 MV photon beam are foreseen.